Why Are Chinese Mothers More Controlling Than American Mothers? "My Child Is My Report Card". Issue 1 (12th April 2013) - Ng, Florrie Fei‐Yin; Pomerantz, Eva M.; Deng, Ciping
<x xml:space="preserve">Abstract</x> Chinese parents exert more control over children than do American parents. The current research examined whether this is due in part to Chinese parents' feelings of worth being more contingent on children's performance. Twice over a year, 215 mothers and children (Mage = 12.86 years) in China and the United States (European and African American) reported on psychologically controlling parenting. Mothers also indicated the extent to which their worth is contingent on children's performance. Psychologically controlling parenting was higher among Chinese than American mothers, particularly European (vs. African) American mothers. Chinese (vs. American) mothers' feelings of worth were more contingent on children's performance, with this contributing to their heightened psychological control relative to American mothers.